csc (π/2) = 1/[sin (π/2) = 1/1 = 1. that is really fundamental.you should know this ! ¶.
http://answers.yahoo.com/question/index?qid=201201...

I assume the expression is cot^2 x / ( csc^2 x  csc x) express it in terms of sin x and cos x: =cos^2 x / sin^2 x) / (1/sin^2 x  1/sin x) =cos^2 x / sin^2 x) / [1  sin x)/sin^2
http://wiki.answers.com/Q/How_do_you_simplify_this...

The expression `(csc^2 A1)/(cot A*csc A)` has to be simplified. `(csc^2 A1)/(cot A*csc A)` => `((1/(sin^2A))1)/((cos A/sin A)*(1/sin A))` => `((1/(sin^2A))1)/(cos A/sin^
http://www.enotes.com/homeworkhelp/whatsimplest...
